2021
DOI: 10.3390/jcm10050897
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Tracking Analysis Reveals Altered Left Atrial and Ventricular Myocardial Deformation in Patients with End-Stage Liver Disease

Abstract: Background: Cardiac function can be influenced by liver cirrhosis and should be thoroughly evaluated before liver transplantation. We investigated left ventricular (LV) and, for the first time, left atrial (LA) strain and strain rate in end-stage liver cirrhosis patients of different etiologies. Methods: This retrospective, cross-sectional study evaluated left heart function in 80 cirrhosis patients and 30 controls using standardized echocardiographic techniques and speckle tracking technology (STE) analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 34 publications
4
27
1
Order By: Relevance
“…This systematic review identified six cross-sectional [ 11 , 15 , 45 48 ], 6 case-control [ 10 , 49 – 53 ], and eight prospective cohort studies[ 14 , 36 , 54 – 59 ] gathered from 12 countries and consisting of 1738 participants ( Table 1 ). Our search strategy did not identify any randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review identified six cross-sectional [ 11 , 15 , 45 48 ], 6 case-control [ 10 , 49 – 53 ], and eight prospective cohort studies[ 14 , 36 , 54 – 59 ] gathered from 12 countries and consisting of 1738 participants ( Table 1 ). Our search strategy did not identify any randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…We found one cross-sectional [ 15 ], one case-control [ 53 ], and three prospective cohort studies [ 14 , 55 , 59 ] providing results for GLS in both ventricles. There were four cross-sectional [ 11 , 45 , 46 , 48 ], five case-control [ 10 , 49 52 ], five prospective cohort studies [ 36 , 54 , 56 58 ] providing results only for the left ventricle. Meanwhile, one cross-sectional study [ 47 ] providing result only for the right ventricle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show a correlation between abnormal GLS and mortality in patients with advanced cirrhosis. (8,9) There are some limitations of the Razpotnik et al study. They did not compare the prevalence of CCM among those with different severities of cirrhosis.…”
Section: Ring Out the Old Ring In The Newmentioning
confidence: 93%
“…Recent studies show a correlation between abnormal GLS and mortality in patients with advanced cirrhosis. ( 8,9 )…”
Section: Criteria Systolic Dysfunction Diastolic Dysfunctionmentioning
confidence: 99%